Immediate Placement and Restoration of a New Tapered Implant System in the Aesthetic Region: A Report of Three Cases - Caroliene M. Meijndert; Gerry M. Raghoebar; Arjan Vissink; Henny J. A. Meijer (Case Reports in Dentistry)
Objective. To assess the clinical, radiographic, aesthetic, and patient-centred outcomes of a new implant system applied for an immediate implant placement and restoration approach in single tooth replacement of anterior maxillary teeth. Material and Method. Three cases were treated with a bone level tapered implant. All patients were treated with the same strategy involving flapless extraction and implant placement with simultaneous augmentation. Implants were provisionally restored with a screw-retained restoration at the day of surgery. Definitive restoration was fabricated after 3 months. Follow-up was one year after definitive restoration. Results. At the 1-year follow-up, the implants were stable and no complications had occurred. Peri-implant bone levels had increased with a mean value of 0.24±0.30 mm between definitive restoration placement and 1 year of follow-up. Clinical outcome scores showed healthy soft tissues. Mean Pink and White Esthetic scores were rated 7.0 and 7.3, respectively. Mean patient satisfaction had improved from 55.7 (pretreatment) to 90.0 (1-year follow-up) on a 0-100 VAS scale. Conclusion. Immediate implant placement and restoration with the new tapered bone level implant system are accompanied by good initial clinical and radiographic results as well as high patient satisfaction.